Peran Orang Tua Dalam Menanggulangi Anak yang Kecanduan Narkoba di Desa Aek Tapa Kecamatan Merbau Kabupaten Labuhan Batu Utara - Muhammad Ilham Sitompul; Kamalia (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The aim of this research is to analyse the role of parents in the prevention and mitigation of drug addiction in Aek Tapa Village, Merbau District, North Labuhan Batu Regency. In data collection, the method used in this study employs interviews with a descriptive qualitative approach. This research shows that the role of parents is crucial in protecting children from the dangers of drugs, both in prevention and mitigation efforts. Parents act as educators by providing early education about the dangers of drugs through discussions at home and real-life examples from the surrounding environment. Strict supervision of children's interactions and activities is an important strategy in preventing negative influences from the external environment. In addition, open communication between parents and children is key in building trust and preventing children from feeling alienated, which often becomes a triggering factor for drug abuse. In terms of intervention, parents provide significant emotional and psychological support to help their children through the recovery process.